School discipline and the delictual negligence test for teachers – a case in point - Potgieter, J. M. (Faculty of Law, University of the Free State, 2015)
No abstract available
Peet Gouws v Laerskool Lynnwood & MEC for Education, Gauteng case no. 3223/11 (24 October 2012) (GP)
Keywords: School discipline; Negligence